Dampak Psikologis dari Kekerasan dalam Rumah Tangga terhadap Perempuan pada Budaya Patriarki di Bali - Ni Made Putri Ariyanti; I Ketut Ardhana (Pusat Kajian Bali Universitas Udayana, 2020)
The Balinese who still maintain their cultural traditions are inseparable from the patriarchal culture with a patrilineal system which is clearly seen in married life that embraces the concept of purusa (men as a head of the family). Society is characterized by patriarchal culture which seems to dominate the position of men in decision making that raises the problem of domestic violence. This study analyzes psychological impact for those women who experienced domestic violence in patriarchal culture. This study used qualitative research with case study approach and the number of the respondents was three Balinesse women experiencing domestic violence. The data collected from interview and observation. This study concludes that patriarchal cultural became one of the causes of violence and psychological impacts that experienced by the three cases were feelings of fear, negative thoughts about themselves, feelings of worthlessness, feelings of depression, and release their anger to the child.Keywords: patriarchal culture, domestic violence, Balinesse family, psychological approach, Balinesse women